Influence of dietary niacin on starter pig performance - D E Real; B W James; E Alonso; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
Two experiments were conducted using 415 weanling pigs (175 in Exp. 1, 240 in Exp. 2) to determine the influence of dietary niacin inclusion on starter pig performance. Pigs were fed a control diet with no added niacin or the control diet with 25, 50, 75 or 100 g/ton of added niacin. From d 0 to 8, increasing dietary niacin increased ADG and ADFI up to 50 g/ton of added niacin. Overall, pigs fed increasing levels of niacin tended to have improved ADG. These results suggest feeding 50 g/ton of added dietary niacin to complex nursery pig diets to improve growth performance.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Niacin; Starter; Performance